Dark side of business-to-business (B2B) relationships - Sharma, Piyush; Kingshott, Russel; Leung, Tak Yan; Malik, Ashish (Elsevier, 2022)
Despite growing research on the dark side of B2B relationships in the last two decades, there are still many gaps in this literature, which need to be addressed to provide a more complete understanding of the various dark side phenomena and the associated processes. This special issue addresses this need with 27 articles (including five invited articles), classified along seven distinct themes, including a) relationship characteristics and behaviors, b) process-view of dark side, c) coopetition and co-creation, d) channel partners and suppliers, e) internationalization and governance, f) certification and governance in finance sector, and g) role of emerging technologies. We begin this editorial by reviewing the dark side of B2B relationships literature to identify specific research gaps. Next, we describe the 27 articles and their findings, classified under the seven themes. Finally, we discuss their contributions and implications with some useful directions for future research on this important topic.